The impact of certain parental treatment styles on the emergence of learning difficulties among primary school pupils: an analytical approach. - toumi, tayeb (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : The current study aimed to know the effect of some parenting methods on the emergence of learning difficulties for a student, As the authors of this research paper tried to show some of the parenting methods they use with their educated and represented children: In style Negligence, excessive protection, and stimulus, And after our reading of some previous studies that were a starting point for our current research and support for researchers in their literary presentation and during the analysis of the results. In the last thing that we wanted to present is our assertion that these parenting methods, despite their negative aspects, especially on the pedagogical side, may be a direct cause of educational difficulties among their children, And what we have to clarify in our analysis is to clarify the effect of these methods on the pupil taught and that many of the family behavioral attitudes give many effects among them on the child’s learning and teaching.